2021
DOI: 10.1186/s12885-021-08683-x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death and effect of non-cancer-specific death on rates of overall survival in adult classic Hodgkin lymphoma: a populated-based competing risk analysis

Abstract: Background The improved prognosis of classic Hodgkin lymphoma (cHL) has been accompanied by elevated risks of non–cancer-specific death (non-CSD). The aim of this study was to verify the occurrence of non-CSD and its effect on rates of overall survival among adult patients with cHL. Methods To ensure sufficient follow-up time, we analyzed retrospective data from patients aged ≥20 years with cHL that was diagnosed between 1983 and 2005 in the Survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…The CVD PMR exceeded that of cHL and other neoplasms with time. This seemed to be opposite to the previous studies that have reported that the proportion of patients who died from cardiovascular disease was lower than that from either HL or other neoplasms 4,25 . Indeed, previous studies only considered the CVD PMR for the entire population rather than analyzing the variation of PMR in different follow‐up intervals; therefore, our results clearly reflected the temporal trend of PMR of CVD among cHL survivors.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…The CVD PMR exceeded that of cHL and other neoplasms with time. This seemed to be opposite to the previous studies that have reported that the proportion of patients who died from cardiovascular disease was lower than that from either HL or other neoplasms 4,25 . Indeed, previous studies only considered the CVD PMR for the entire population rather than analyzing the variation of PMR in different follow‐up intervals; therefore, our results clearly reflected the temporal trend of PMR of CVD among cHL survivors.…”
Section: Discussioncontrasting
confidence: 97%
“…A recent study reported that the cumulative incidence of noncancer‐specific death exceeded that of cancer‐specific death in cHL patients over time. It supported our findings to some extent, although the study did not mention the cumulative incidence of CVD mortality 25 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations